2016
DOI: 10.1371/journal.pone.0155646
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cord Blood Betatrophin Levels in the Offspring of Mothers with Gestational Diabetes

Abstract: AimExposing a fetus to hyperglycemia can increase the risk for later-life metabolic disorders. Betatrophin has been proposed as a key regulator of pancreatic beta cell proliferation and lipid regulation. Highly responsive to nutritional signals, serum betatrophin concentrations have been found to be altered by various physiological and pathological conditions. We hypothesized that betatrophin levels are increased in the cord blood in offspring exposed to intrauterine hyperglycemia.MethodsThis was a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Similarly, Erol et al found the ANGPTL8 level was significantly higher in 45 pregnant women diagnosed with GDM compared with 45 healthy pregnant women matched for BMI and gestational age . Other studies have shown that ANGPTL8 level was increased in the cord blood from women with GDM compared with healthy women at delivery …”
Section: Angptl8 Role In Diabetesmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Erol et al found the ANGPTL8 level was significantly higher in 45 pregnant women diagnosed with GDM compared with 45 healthy pregnant women matched for BMI and gestational age . Other studies have shown that ANGPTL8 level was increased in the cord blood from women with GDM compared with healthy women at delivery …”
Section: Angptl8 Role In Diabetesmentioning
confidence: 88%
“…has been found to be increased in women with gestational diabetes (GDM) either in blood circulation 57,[59][60][61] or cord blood 60,61 as summarized in Table 2. Consistently, ANGPTL8 has been initially shown to be increased during gestation in a mouse model.…”
Section: Angptl8 Role In Diabetesmentioning
confidence: 99%
“…As mentioned above, the impact of betatrophin on insulin resistance seems still far from clear. In recent years, a great deal of researches indicate that there is a positive correlation between this protein and insulin resistance in patients with T2DM, GDM, and other diseases [12][13][14][15][16][17][18][19]. However, many inconsistent findings are also reported in other studies [10,[20][21][22].…”
Section: The Correlation Between Circulating Betatrophin and Insulin mentioning
confidence: 99%
“…Of these studies included, 12 studies recruited patients with T2DM [8, 9, 12-14, 20, 22-27], of which one recruited patients undergoing CD [13], and 5 enrolled GDM [15,16,[28][29][30], 3 enrolled PCOS [17,21,31], 2 enrolled adult with different body weight (BW) [10,32], one enrolled Mets [18] and 2 enrolled NAFLD [19,33]. Twenty-two studies in all included studies were cross-sectional studies, 3 were case control studies.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Several studies revealed that GDM women showed higher levels of betatrophin than control subjects [13–18, 20], indicating that augmented insulin resistance and enhanced insulin demand in GDM may contribute to the upregulation of betatrophin levels. In addition, Natalia et al and Wang et al suggested that not only maternal but also cord blood betatrophin levels were increased in the patients with GDM [16, 18, 29]. Furthermore, the three studies mentioned above found an interesting phenomenon that betatrophin concentration in cord blood was higher than that in maternal serum, which might suggest its role in promoting β-cell proliferation during intrauterine life.…”
Section: Discussionmentioning
confidence: 99%